2011
DOI: 10.1124/dmd.111.042564
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heme Oxygenase-1 Partially Reverses the Arsenite-Mediated Decrease of CYP1A1, CYP1A2, CYP3A23, and CYP3A2 Catalytic Activity in Isolated Rat Hepatocytes

Abstract: ABSTRACT:Heme oxygenase (HO-1), the rate-limiting enzyme in the physiological breakdown of heme, is ubiquitous, and its expression can be increased by arsenite [As(III)], and similar other stimuli that induce cellular oxidative stress. Interestingly, it has been shown that the As(III)-induced HO-1 is inversely correlated with a decrease in cytochromes P450 (P450s) activity; however, the direct role for HO-1 in the inhibition of P450 enzymes remains unknown. Our results showed that As(III) at a concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Similar observations have been reported for alpha-tocopherol inhibited benzo­[ a ]­pyrene-induced CYP1A1 activity, likely as post-translational inhibition, in rat liver microsomes . Moreover, metal-induced heme oxygenase potently inhibited TCDD-induced CYP1A1 enzyme activity in human and rat hepatocytes. Notably, heme oxygenase ( HMOX1 ) transcription was also strongly induced by 3R4F CS exposure at all time points but was only transiently increased (at 4 h) by the THS2.2 aerosol. In intestinal and hepatic cells and in cell-free microsomal systems, it has been demonstrated that reduced mRNA and protein levels of cytochrome P450 (CYP) oxidoreductase (POR) (an important electron donor for all CYPs) can significantly lower CYP activities including CYP1A1. In the 3R4F CS-exposed organotypic oral epithelial cultures, there was no consistent downregulation of POR expression, only a weak decrease for the lower concentration at the 72-h time point (Figure ), that could explain the post-transcriptional inhibition of CYP1A1/1B1 activity.…”
Section: Discussionsupporting
confidence: 75%
“…Similar observations have been reported for alpha-tocopherol inhibited benzo­[ a ]­pyrene-induced CYP1A1 activity, likely as post-translational inhibition, in rat liver microsomes . Moreover, metal-induced heme oxygenase potently inhibited TCDD-induced CYP1A1 enzyme activity in human and rat hepatocytes. Notably, heme oxygenase ( HMOX1 ) transcription was also strongly induced by 3R4F CS exposure at all time points but was only transiently increased (at 4 h) by the THS2.2 aerosol. In intestinal and hepatic cells and in cell-free microsomal systems, it has been demonstrated that reduced mRNA and protein levels of cytochrome P450 (CYP) oxidoreductase (POR) (an important electron donor for all CYPs) can significantly lower CYP activities including CYP1A1. In the 3R4F CS-exposed organotypic oral epithelial cultures, there was no consistent downregulation of POR expression, only a weak decrease for the lower concentration at the 72-h time point (Figure ), that could explain the post-transcriptional inhibition of CYP1A1/1B1 activity.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, Amara et al (42) reported that the TCDD-mediated induction of CYP1A1 could be inhibited through a posttranslational mechanism in an HO-1-dependent manner. Furthermore, the direct role of HO-1 in the inhibition of CYP1A1 has been reported in rat hepatocytes (43). In our experiment, we showed that the inhibitory effect of Z-Ligustilide on BaP-induced CYP1A1 upregulation was cancelled in the Nrf2 knock-down condition, suggesting that the Nrf2 activation played an important role in the CYP1A1 inhibition in NHEKs.…”
Section: Discussionsupporting
confidence: 69%
“…These diseases are often marked by oxidative stress and induction of HO-1 leads to a reduction of oxidants (heme) and the production of antioxidants, such as bilirubin and carbon monoxide ( Connick et al, 2021 ). Anwar-Mohamed et al found that that arsenite induces HO-1 expression in rat hepatocytes to mediate CYP1A1, CYP1A2, CYP3A23, and CYP3A2 inhibition ( Anwar-Mohamed et al, 2012 ). HO-1 affects cytochrome P450 function in liver through the formation of heteromeric complex CYP1A2·HO-1 ( Connick, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%